Model Kesetaraan Pendidikan Islam Dalam Sistem Pendidikan Nasional Di Indonesia Tahun 1975 - Wardi Abdul Salam (ISLAMICA, 2017)
Before the integration of Islamic education into the national education system in Indonesia in 1975 occurred the dichotomy of Islamic education and general education. In order to eliminate the dichotomy of education is done by following the tendency that occurs. The trend is from pesantren to Madrasah, and from Madrasah to school; from a dichotomy to a uniform and integrated system of education is realized and controlled in one hand of government, with one common policy for all. Recognition of the existence of Madrasah education is then followed adjustments to the school system in general. The initial process will be followed by the release of the Joint Ministerial Decree of the Minister of Religion, the Minister of Education and Culture, and the Minister of Home Affairs in 1975 which has implications for Islamic education and education within the framework of the national education system of Indonesia.